Pergeseran Perilaku Politik Kiai dan Santri di Pamekasan Madura - Zainuddin Syarif (AL-TAHRIR, 2016)
Abstract, this research applied qualitative approach, by using field research model. The qualitative approach model that is applied emphasize more on Phenomenological perspective, which is focus on the interpretation and emic meaning analysis in the forms of expressions (empiric) found in the field.  While the focus of this research concists of (1) what is the meaning of "politic" for Kiai and Santri Pamekasan? (2) How is the tendency of Santri’s political attitude to the Kiai’s political attitude? (3) How are the ways and efforts taken by Kiai to defend their autoritative leadership?. This research took place in Palengaan district, Pamekasan regency where the focus of this study is the Kiai’s involvement and santri in the politic on regent and vise regent election in 2008 – 2013 period (Local Leaders Election), that is held on 5 March 2008 and on 9 January 2013 – 2018 period. The results of this research are: the first, the Kiai’s political formula is used to retain his leadership authority to Santri which relies on two powers, they are; traditional  and charismatic domination.  It means Kiaikeeps to retain his glamour as religious charismatic figure by using the symbols of obedience which are framed by religious moral values in retaining his santri’s obedience. Second, Santri’ political attitude have shifted from political obedience to the political difference although it is done by alumnus only. From their political attitude, it is found that there are three Santri’s political typology, they are: (1) Santri with absolute obedience, (2) Santri with fictive obedience, (3) Prismatic Santriالملخص:استخدم هذا البحث المنهج النوعي بالإطار الميداني. فيطلق المنهج النوعي على وجهة النظر الفينومنولوجية التي تؤدي إلى تفسير وتحليل المعنى الداخلي الذي يتعلق بالعبارات الموجودة فى الميدان. أما تحديد هذا البحث فيطلق إلى ما يلي: 1) ما هو معني السياسة عند أسياد المعاهد الإسلامية وطلابها فى مدينة باميكاسن؟ 2) إلى ما اتجهت سلوك السياسة لطلاب المعاهد الإسلامية نحو انتخاب أسياد المعاهد السياسي؟ 3) ما هي المحاولات والمواقف لأسياد المعاهد على محافظة سيطرتهم الرياسية؟ حل هذا البحث فى منطقة بالنجاعن بمحافظة باميكاسن بالتركيز إلى مشاركة أسياد المعاهد وطلابها فى سياسة انتخاب رئيس المحافظة ونائبها بمرحلة السنة 2008- 2013 من الميلاد ، المعقدة تاريخ الخامس من مارس سنة 2008 م وفى  فترة بين شهر يناير 2008 إلى يناير 2018. فالاستنتاجات من هذا البحث هي: 1) صيغة أسياد المعاهد السياسية المستخدمة فى محافظة سيطرتهم الرياسية على جميع الطلاب تركز إلى القوتين، هما: التقليدية و الهيمنة الكاريزمية. فهما تعنيان أن أسياد المعاهد يحافظ أنفسهم كأشخاص كاريزمي متدين برموز الطاعات مع إطارات القيم الدينية فى محافظة طاعات الطلاب نحوهم. 2) وقوع التغييرات فى الاتجاهات السياسية لطلاب المعاهد من الإطاعة السياسية إلى التفرق السياسي، رغم أن ذلك منفذ فى المجالات المحدودة (فرقة الخريجين). فمن قبل الاتجاهات المتنوعة، أوجد الباحث ثلاثة أنواع الطلاب: 1) الطلاب المطيع فى الدرجة المطلقة، 2) الطلاب المطيع فى الدرجة الزائفة، 3) الطلاب البرسماتيكية.Abstrak: penelitian ini menggunakan pendekatan kualitatif, dengan model penelitian lapangan. Model pendekatan kualitatif yang digunakan lebih menekankan pada perspektif fenomenologi, yaitu penekanan kepada interpretasi dan analisis makna emic yang berupa ungkapan-ungkapan (empiris) yang ditemukan di lapangan. Adapun, fokus penelitian ini terdiri dari: (1) Apa makna politik bagi kiai dan santri di Pamekasan? (2) Bagaimana  kecenderungan perilaku politik santri terhadap pilihan politik kiai?  (3) Bagaimana upaya dan sikap kiai mempertahankan otoritas kepemimpinannya? Riset ini mengambil tempat di Kecamatan Palengaan, Kabupaten Pamekasan dengan fokus kajian keterlibatan kiai dan santri dalam politik pemilihan  bupati dan wakil bupati periode 2008-2013 (Pilkada), yang dilaksanakan pada tanggal 5, Maret 2008 dan periode 9 Januari 2013-2018. Hasil penelitian ini adalah: Pertama, formula politik kiai yang digunakan dalam mempertahankan otoritas kepemimpinannya terhadap santri bertumpu pada dua kekuatan yatu; traditional dan charismatic domination. Artinya kiai tetap mempertahankan pesona sebagai sosok karismatik relijius melalui simbol-simbol kepatuhan yang dibingkai nilai moral agama dalam mempertahankan kepatuhan santrinya.  Kedua, perilaku politik santri telah terjadi pergeseran dari kepatuhan politik ke perbedaan politik walaupun hal itu dilakukan oleh sebatas santri alumni. Dari perilaku politik santri tersebut  ditemukan   ada tiga tipologi politik santri yaitu: (1) Santri patuh mutlak, (2) Santri patuh semu dan (3) Santri prismatik.